PENGARUH AUDIT TENURE, AUDIT LAG, OPINION SHOPPING, LIQUIDITY, LEVERAGE, DAN DEBT DEFAULT TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Empiris pada Perusahaan Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Ahmad Hafidz Fikri Azhar; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of audit tenure, audit lag, opinion shopping, liquidity, leverage, and debt default on going concern audit opinion. This study has a dependent variable, namely going concern audit opinion with independent variables including audit tenure, audit lag, opinion shopping, liquidity, leverage, and debt default. This study uses secondary data derived from the financial statements of all energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The research sampling was carried out using purposive sampling method. A total of 61 companies were tested with details of 180 samples throughout the three-year research span. The analysis method used is logistic regression analysis. The results of this study indicate that liquidity has a negative effect, while leverage, and debt default have a positive effect on going concern audit opinion acceptance while audit tenure, audit lag, and opinion shopping are found to have no effect.